An Analysis of Opportunities Connected with the Utilization of Web 2.0 Technologies in Knowledge Management Systems of Contemporary Organizations - Wielki, Janusz (Advanced Information Technologies for Management – AITM 2009, 2009)
The paper is devoted to the problem of the utilization of technologies called "Web 2.0 technologies" for knowledge management during the transformation of the contemporary economy to its post-industrial phase. The paper is composed of four parts. The first concentrates on the changes taking place in the contemporary economy. Next, the role of knowledge as a key resource from the point of view of organizations functioning in the post-industrial reality has been presented. The third part is the most crucial one and is focused on the presentation and analysis of the opportunities connected with the utilization of Web 2.0 technologies in the process of knowledge management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 207-215